In awe of the Holy City: Mecca in the eyes of five medieval travellers - Widodo, Aditya Pratama; Alwi, Alwi (IIUM Press, 2024)
This paper elaborates and analyses the situation of Mecca between the 11thto 16th centuries based on travel accounts of five medieval travellers: Ibn Khusraw (1004–1072), Ibn Jubayr (1145–1217), Ibn Battuta (1304–1369), Ma Huan (1380–1460) and di Varthema (1470–1512). Moreover, by thoroughly consulting primary sources scored by above-mentioned travellers and other relevant secondary sources, this study aims to ascertain the importance of Mecca, in the given period, in the eye of Muslims and non-Muslim travellers. As the holiest city in Islam, which is also associated with Muslim religious pilgrimages, Mecca has a long and intriguing history throughout the ages. Furthermore, more often than not, during the medieval period, the pilgrimages to Mecca, which are usually conducted during the Islamic month of Dzulhijjah, were haunted by challenges and dangers posed by natural and social environments in and around Mecca, thus made the journey experiences of above-mentioned travellers all the more challenging, precious and memorable. However, at the end of the day, their hardships paid off and their praises proclaimed since they found themselves drenched in joy and in awe of the beauty and greatness of the Holy City. This research uses historical methodology, focusing on primary texts written by the five pilgrims mentioned above. This study provides a more comprehensive picture of the condition of the Holy City of Mecca in the era under study.